Peran Budaya Organisasi Dalam Membangun Kolaborasi dan Inovasi Ditempat Kerja - Fania Rahma Yunanda; Wildan Ansori Hasibuan; Pangesti Harmiza Putri; Syahfitri Syahfitri (Jurnal Ilmiah Dan Karya Mahasiswa, 2025)
This study aims to examine the relationship between organizational culture, collaboration, and innovation in improving organizational performance. Through a qualitative approach with a case study method, this study explores how the formed organizational culture affects interactions between employees, the implementation of collaboration, and the creation of innovation. Data were collected through in-depth interviews, observations, and documentation analysis at PT Citra Kesawan Selaras. The results of the study indicate that an organizational culture that supports effective collaboration can facilitate the creation of innovation, which in turn contributes to increased employee productivity and performance. This study provides important insights for companies in creating a productive and innovative work environment through proper management of organizational culture.